The evolution of the student as a customer in Australian higher education: a policy perspective - Pitman, Tim (Australian Association for Research in Education, 2016)
In 2014, the Australian Federal Government attempted to de-regulate higher education fees so as to allow universities to set their own tuition fees. The associated public debate offer critical insights into how the identity of a student as a ‘customer’ of higher education is understood and deployed when developing higher education policy. This paper uses the 2014 Australian higher education reforms as a lens through which to further scholarly research into the student-as-customer metaphor and to see how it is influenced by the perceptions and understandings of policy actors external to the higher education sector. These include politicians, special interest groups, the students and their parents and prospective employers. This study reveals that the public/private nexus—both of funding and benefit— problematizes traditional conceptualisations of students and others as higher education customers. In turn, this restricts the ability or desire of policy actors to describe how the student functions as a customer as a consequence of market reform. This inability compromises the development of effective and sustainable higher education policy